Análisis de diferencias en puntajes en la prueba ENLACE entre niños y niñas en el sistema escolar mexicano - Campos Vázquez, Raymundo M.; Santillán Hernández, Alma S. (El Colegio de México, A.C., 2016)
This paper analyzes the gender gap in standardized test scores in Mexico. The data used comes from the ENLACE test for primary, junior high and high school. In primary and junior high school, girls perform better than boys in both spanish and math across the test score distribution, but in the top part of the math score distribution. In high school, across the test score distribution, girls perform better than boys in spanish and the opposite occurs in math.